Global epidemiological characteristics of malnutrition in cancer patients: a comprehensive meta-analysis and systematic review - Jinhui Zhang; Yumeng Quan; Xiaolin Wang; Xiaolei Wei; Xueli Shen; Xue Li; Tao Liang (BMC Cancer)
Abstract Background & aims The epidemiological characteristics of malnutrition in cancer patients remain unclear. The Global Leadership Initiative on Malnutrition (GLIM) criteria, published in 2019, were established to compare the prevalence of malnutrition globally, drive the development of standardized care practices, and promote improved clinical outcomes. This study aimed to systematically assess the prevalence and related factors of malnutrition in cancer patients based on the GLIM criteria, and to evaluate its association with clinical outcomes. Methods Two authors independently searched PubMed, Web of Science, the Cochrane Library, and Embase up to July 20, 2024. Eligible studies were observational (cross-sectional or cohort), involved adult cancer patients, and assessed nutritional status using the GLIM criteria. Studies were required to report at least one of the following outcomes: prevalence of malnutrition, associated factors, or relevant clinical outcomes. Heterogeneity was assessed using the I² and Q tests. A random-effects model was used when significant heterogeneity was present (I²>50%, P < 0.05); otherwise, a fixed-effects model was applied. PROSPERO registration number: CRD420251053345. Results A total of 20 cross-sectional studies and 45 cohort studies were included, all of which reported the prevalence of malnutrition and together covered over 30,000 cancer patients. Three studies examined factors influencing malnutrition. Nine studies evaluated its impact on overall survival (OS), while three assessed its effect on postoperative complications. Overall, the prevalence of malnutrition was 41% (95% CI: 36-45%), with moderate malnutrition at 19% (95% CI: 16-23%) and severe malnutrition at 20% (95% CI: 17-23%). The main factors influencing malnutrition in cancer patients were tumor-related symptoms. Malnutrition in cancer patients is significantly associated with OS (HR = 2.04, 95% CI: 1.56–2.67). Specifically, the risk is significantly increased in patients with moderate malnutrition (HR = 1.34, 95% CI: 1.07–1.72), and even higher in those with severe malnutrition (HR = 1.92, 95% CI: 1.55–2.39). Additionally, malnutrition in cancer patients is also significantly associated with an increased risk of postoperative complications (OR = 1.90, 95% CI: 1.41–2.55). Conclusion Malnutrition prevalence is high among cancer patients, primarily due to tumor-related symptoms. It significantly increases the risk of poor clinical outcomes, with a more pronounced effect in patients suffering from severe malnutrition.